Implementation of the Profile Matching Method in a Football Player Position Decision Support - Handayani, Tri Pratiwi; Poha, Rahmad A; Ibrahim, Irawan; Ghani, Hilmasyah (Journal of Information System, Technology and Engineering, 2024)
This study aims to overcome this issue by objectively determining the best positions of the soccer players through the application of the Profile Matching technique. The process consists of five steps: GAP values are first determined by comparing each player's unique traits to predetermined benchmarks. Next, compute the primary and secondary standards, establish weighted scores by utilizing the GAP values, compute the GAP values by contrasting specific player attributes with predetermined benchmarks, compute the overall scores, and order players according to their performance. A weighted combination of mental, physical, and skill criteria (30, 40%, and 30%, respectively) determines the final positions. The results demonstrate how effectively this rigorous technique scores the participants. This process offers a logical and objective approach to player selection, enhancing the precision and effectiveness of decision-making in soccer team management.